Change in mandibular body height at the site of a fixation plate in the advance (lengthening) and setback (shortening) sides after sagittal split ramus osteotomy. Issue 3 (March 2016) - Ueki, Koichiro; Yoshizawa, Kunio; Moroi, Akinori; Iguchi, Ran; Kosaka, Akihiko; Ikawa, Hiroumi; Tsutsui, Takamitsu; Saida, Yuriko; Hotta, Asami
Abstract: Purpose: The purpose of this study was to evaluate changes in mandibular body height at the site of a fixation plate in the advance (lengthening) and setback (shortening) sides after sagittal split ramus osteotomy (SSRO). Subjects and methods: The subjects were 49 patients (98 sides) who underwent bilateral SSRO surgery. The subjects were divided into 4 groups as follows, setback (shortening) sides in mandibular prognathism (Prog S group; n = 42), advancement (lengthening) sides in mandibular retrognathism (Retro L group; n = 24), setback (shortening) sides in mandibular asymmetry (Asym S group; n = 16) and advancement (lengthening) sides in mandibular asymmetry (Asym L group; n = 16). Postoperative computed tomography (CT) was analyzed for all patients pre-operatively, and at 1 week and 1 year postoperative. Mandibular body height at the site of the fixation plate, mandibular upper height above the plate and mandibular lower height under the plate were measured by 3-dimensional (3D) CT. Results: There were no significant differences in mandibular height between the lengthening and shortening sides in mandibular prognathism, retrognathism and asymmetry in the time-course change. Upper mandibular height at the mid-point of the fixation plate after 1 year was significantly smaller than that after 1 week in all sides (P < 0.05). Conclusion: This study suggested that slight bone resorption could occur at the upper site of a fixation plate after set back and advancement SSRO.